Linkages between multinationals and indigenous firms: evidence for the electronics sector in Ireland - Holger Görg; Frances P. Ruane (Trinity College, Department of Economics, 1998)
This paper analyses the concept of linkages and studies the development and the determinants of inter-firm linkages between electronics firms in Ireland and domestic sub-suppliers using firm level data for 1982 to 1995. We discuss the concept of inter-firm linkages and the effects of linkages. We argue that the concept of linkages developed by Hirschman (1958) is an inter-sectoral concept which can arise as a result of underlying inter-firm linkages. Our empirical analysis indicates that foreign-owned electronic firms in Ireland source, on average, 24 per cent of their inputs in Ireland, which compares favourably with an estimate for foreign firms in Scottish electronics industries. In an econometric estimation, using panel data techniques, we find that firms in the Irish electronics sector increase their backward linkages over time; that foreign firms have lower linkages than Irish-owned firms; and that large and expanding firms have lower linkages than other firms.
Keywords: L63; O14; R34; 330; Multinationales Unternehmen; Lieferanten-Kunden-Beziehung; Elektronikindustrie; Schätzung; Irland